Recepción del pensamiento moderno europeo y enseñanza de la filosofía en el siglo XVIII en el Río de la Plata. El caso de Baruch Spinoza (2022)
This paper aims to address the reception of modern European philosophy that unfolded in the 18th century in two fundamental institutions in the territory of the Río de la Plata: the Universidad de Córdoba and the Colegio de San Carlos de Buenos Aires. Our aim is to analyze this reception by considering its connection with a specific way of practicing the teaching of philosophy in these institutions, understanding it as an essential part of the philosophical task, as a genuine search for knowledge. We will focus on the case of Baruch Spinoza —a thinker persecuted and condemned to censorship— to illustrate the different ways in which new modern authors were gradually incorporated into the teaching of philosophy in the Rio de la Plata classrooms.